144=-12(X+-60)

Simple and best practice solution for 144=-12(X+-60) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 144=-12(X+-60) equation:


Simplifying
144 = -12(X + -60)

Reorder the terms:
144 = -12(-60 + X)
144 = (-60 * -12 + X * -12)
144 = (720 + -12X)

Solving
144 = 720 + -12X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '12X' to each side of the equation.
144 + 12X = 720 + -12X + 12X

Combine like terms: -12X + 12X = 0
144 + 12X = 720 + 0
144 + 12X = 720

Add '-144' to each side of the equation.
144 + -144 + 12X = 720 + -144

Combine like terms: 144 + -144 = 0
0 + 12X = 720 + -144
12X = 720 + -144

Combine like terms: 720 + -144 = 576
12X = 576

Divide each side by '12'.
X = 48

Simplifying
X = 48

See similar equations:

| a*bcd=bcd*a | | 1X+8=3X+14 | | (x+y)=3(x+y)-2 | | 4x-(3x-7)-(2x-3)=8x(x-1) | | 8z+4=11z-17 | | 3x+4(1)=-2 | | 5(2u-2)-12u= | | 5m+2n-2m+9n= | | 2x+12=3x-8 | | 9+3r=-17 | | -72+11y+2=4(5y-2)-8 | | -2(2-5x)=8x-2 | | 14qp-51q^2+p^2= | | -5x-3x+9x=4-x | | 1/2x=1/4-6 | | w/7=3=-1 | | 2(2-5x)=8x-2 | | 13=-10y+3y | | 4(x-3)(x+4)=0 | | 5y-y=-12+y | | 2.5=(x-54166)/10200 | | 4(5x-3)+9=-2 | | (6x+2)(7x^2-5x-4)= | | 2x-10=38 | | -9r+1=-80 | | 3x8/3 | | mx^2+(2m-1)x+(m-1)=0 | | 5=x/4=1 | | 16=-10b+3b | | x^3-5x=-3 | | -8x-8=9x+43 | | 8(y-1)+5(y-1)= |

Equations solver categories